Compartmentalization of a Multidrug-Resistant Cytomegalovirus UL54 Mutant in a Stem Cell Transplant Recipient with Encephalitis. (13th June 2019) - Piret, Jocelyne; Schibler, Manuel; Pham, Van Dung; Hantz, Sébastien; Giannotti, Federica; Masouridi-Levrat, Stavroula; Kaiser, Laurent; Goyette, Nathalie; Alain, Sophie; Shi, Rong; Boivin, Guy
Abstract: We report a case of cytomegalovirus encephalitis in a hematopoietic stem cell transplant recipient. A previously uncharacterized V787E mutation in UL54 was identified in cerebrospinal fluid but not plasma specimens. For the V787E recombinant virus, the half maximal effective concentrations for ganciclovir, foscarnet, and cidofovir were 8.6-, 3.4- and 2.9-fold higher than for wild-type virus, and the replicative capacity was lower. The introduction of a bulkier and negatively charged glutamate residue at position 787 could destabilize the finger domain of UL54 DNA polymerase. Viral genotyping of cerebrospinal fluid is warranted in subjects with cytomegalovirus encephalitis, owing to the low penetration of antivirals in this compartment. Abstract : A compartmentalized multidrug-resistant cytomegalovirus with an uncharacterized UL54 mutation (V787E) was identified in cerebrospinal fluid but not plasma specimens from a hematopoietic stem cell transplant recipient. This observation suggests the importance of performing viral genotyping in cerebrospinal fluid specimens from patients with cytomegalovirus encephalitis.